Faktor Penyebab Ketidaklengkapan Pengisian Dokumen Rekam Medis Rawat Inap di Rumah Sakit - Alfiansyah, Gamasiano; Pratiwi, Dita Melinda; Nuraini, Novita; Nurmawati, Ida (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
One of the characteristics of good medical record management is a complete medical record. This study aims to determine the factors causing the incomplete filling of inpatient medical record documents. The method used in this study was a literature review with 15 journal articles that had been selected according to the inclusion criteria. The results showed that there were several factors causing incomplete filling of inpatient medical record documents as seen from the "man" factor, namely lack of knowledge of officers, indiscipline of officers, lack of motivation of officers, high workload, and no training. The "machine" factor is the lack of communication between officers, the absence of monitoring and evaluation of medical records, and the absence of sanctions or rewards. The "method" factor, namely the implementation of filling out inpatient medical record documents is not in accordance with the SOP (Standard Operating Procedure). The "material" factor, namely medical record documents need to be simplified, there is no special room to fill in medical records, and there is no incomplete recapitulation data and the "money" factor, namely a limited budget. Hospitals need to pay attention to these factors so that they can maintain the quality of service and the quality of hospital medical records.Keywords: medical record documents; incompleteness; inpatient ABSTRAK Salah satu ciri penyelenggaraan rekam medis yang baik adalah rekam medis yang lengkap. Penelitian ini bertujuan untuk mengetahui faktor penyebab ketidaklengkapan pengisian dokumen rekam medis rawat inap. Metode yang digunakan dalam studi ini adalah literature review dengan 15 artikel jurnal yang telah dipilih sesuai dengan kriteria inklusi. Hasil penelitian menunjukkan bahwa ada beberapa faktor penyebab ketidaklengkapan pengisian dokumen rekam medis rawat inap yang dilihat dari faktor “man” yaitu kurangnya pengetahuan petugas, ketidakdisiplinan petugas, kurangnya motivasi petugas, beban kerja yang tinggi, dan tidak ada pelatihan. Faktor “machine” yaitu kurangnya komunikasi antar petugas, belum adanya monitoring dan evaluasi mengenai rekam medis, dan tidak adanya sanksi atau penghargaan. Faktor “method” yaitu pelaksanaan pengisian dokumen rekam medis rawat inap belum sesuai dengan SOP (Standard Operating Procedure). Faktor “material” yaitu dokumen rekam medis perlu disederhanakan, tidak adanya ruangan khusus untuk mengisi rekam medis, dan tidak ada data rekapitulasi ketidaklengkapan dan faktor “money” yaitu anggaran dana yang terbatas. Rumah sakit perlu memperhatikan faktor-faktor tersebut sehingga dapat menjaga mutu pelayanan serta mutu rekam medis rumah sakit.Kata kunci: dokumen rekam medis; ketidaklengkapan; rawat inap